Compact CPW-Fed Broadband Circularly Polarized Monopole Antenna With Inverted L-Shaped Strip And Asymmetric Ground Plane - Alsariera, Hussein Salameh Mahmoud; Zakaria, Zahriladha; Awang Md Isa, Azmi; Al-Heety, Othman Saad; Zeain, Mohammed Yousif; Al-Ahnomi, Rammah Ali Hussien; Mussa Buharg, Mussa Mabrok; Abu-Khadrah, Ahmed Ismail Mohammad (Wydawnictwo SIGMA-NOT, 2020)
The design of a coplanar waveguide-fed (CPW-fed) broadband circularly polarized printed monopole antenna is proposed. The antenna consists of a simple rectangular radiator monopole, an inverted L-shaped strip, a horizontal stub, and a modified asymmetric ground plane. Simulation results indicate that the impedance bandwidth (IBW) is 121% (1.575-6.4 GHz), and the axial ratio bandwidth (ARBW) is 64.3% (2.85-5.55 GHz). A parametric study is performed for verification. Results: indicate that the proposed antenna is suitable for different wireless communications systems.